EFFECT OF SUBSTITUTION RATIOS OF FAT ON CHARACTERISTICS OF SIMI-ICE MILK - S. KH. BADAWI; S. A. MOHAMMMED (Mesopotamia Journal of Agriculture)
This study was performed to investigate the effect of partial or complete substitution of fat in blends of dairy ice cream with two semi fat sources namely; dry whey and microcrystalline cellulose (MCC). Results show that there was , an increase in the rate of total solid content, total sugars, ash, protein and yield and a decrease in pH value in whey blends compared to the blends of MCC in which fibers content was increased with increasing the ratio of substitution. Results also show that specific weight of whey blends increased compared to that of MCC blends which showed an adverse trend in was specific weight value. Further, result show an increase in viscosity through aging. Moreover there was an increase in the shrinkage values only in the whey blends after 24hr the storage time, whereas freezing point was increase only in the MCC blends. Furthermore the result also showed that MCC blends was more resistant to melting point and more reduced in energy content compared with whey blends. Whereas whey blends revealed higher degree in sensory evaluation than that of other blends.